Propuesta de adaptación de la Técnica Junguiana del Sandplay (caja de arena) para el trabajo terapéutico relacionado con las demandas de ánimo bajo y agresividad presentes en los casos asignados del Centro de Referencia “Mi Caleta” durante los meses de Julio a Octubre de 2015. - Mayorga Torres, María Fernanda (2016)
This project proposes the analysis of working with the demands of low mood and aggression present in the cases that were assigned in the course of pre-professional practice, through the use of Jungian Technique of Sandplay during contextualizing its use and application for the target population of the project described here. This seeks to achieve resonance dimension that the Technical Jungian Sandplay can have under the Jungian theory’s light with the population. For this, there were described concepts that will be useful for a better understanding of this intervention, these concepts are: projection, opposed, self-regulation and structure of the psyche, personal and collective unconscious, complexes and archetypes. Sandplay Jungian Technique as a projective technique allows the subject to reflect his psychic reality through unstructured stimulus, which facilitates working with the subjectivity of children as well as the unconscious material that can be found as latent behind the demonstrations that might relate to such psychic conflicts that cause discomfort to individuals and their environment. By analyzing the information, assumptions were made about the self, the orphan’s archetype and the interpretation of spatial phenomenon reflected in the subjectivity of the population towards which was directed this project.